Efeito imediato e a curto prazo do cigarro sobre o transporte mucociliar nasal de fumadores - Proenca, M. [UNESP]; Fagundes Xavier, R. [UNESP]; Ramos, D.; Cavalheri, V. [UNESP]; Pitta, F. [UNESP]; Cipulo Ramos, E. M. [UNESP] (Soc Portuguesa Pneumologia, 2011)
Background and objectives: The efficiency of mucociliary transport may vary in different conditions, such as in exposure to harmful particles of the cigarette smoke. The present study evaluated the acute and short term effects of smoking on nasal mucociliary clearance in current smokers by the quantification of the Saccharin Transit Time (STT), and to investigate its correlation with the history of tobacco consumption.Methods: Nineteen current smokers (11 men, 51 +/- 16 years; BMI 23 +/- 9 kg/m(2), 27 +/- 11 cigarettes per day, 44 +/- 25 pack-years), entering a smoking cessation intervention program, responded to a questionnaire concerning smoking history and were submitted to lung function assessment (spirometry) and the STT test. STT was assessed immediately after smoking and 8 hours after smoking. The STT test was also performed in nineteen matched healthy non-smokers' who served as control group.Results: When compared to STT in non-smokers' (10 +/- 4 min; mean +/- standard deviation), smokers presented similar STT immediately after smoking (11 +/- 6 min; p = 0.87) and slower SIT 8 hours after smoking (16 +/- 6 min; p = 0.005 versus non-smokers' and p = 0.003 versus immediately after smoking). STT 8 hours after smoking correlated positively with age (r = 0.59; p = 0.007), cigarettes per day (r = 0.53; p = 0.02) and pack-years index (r = 0.74; p = 0.0003).Conclusions: In smokers, although the mucociliary clearance immediately after smoking is similar to non-smokers', eight hours after smoking it is reduced, and this reduction is closely related to the smoking habits. (C) 2010 Sociedade Portuguesa de Pneumologia. Published by Elsevier Espana, S.L. All rights reserved.
Immediate and short term effects of smoking on nasal mucociliary clearance in smokers
Keywords: Mucociliary clearance; Smoking; Saccharin sodium